USP22 Induces Cisplatin Resistance in Lung Adenocarcinoma by Regulating γH2AX-Mediated DNA Damage Repair and Ku70/Bax-Mediated Apoptosis - Wang, Aman; Ning, Zhen; Lu, Chang; Gao, Wei; Liang, Jinxiao; Yan, Qiu; Tan, Guang; Liu, Jiwei (Frontiers in Pharmacology, 2017)
Resistance to platinum-based chemotherapy is one of the most important reasons for treatment failure in advanced non-small cell lung cancer (NSCLC), but the underlying mechanism is extremely complex and unclear. The present study aimed to investigate the correlation of ubiquitin specific peptidase 22 (USP22) with acquired resistance to cisplatin in lung adenocarcinoma. In this study, we found that overexpression of USP22 could lead to cisplatin resistance in A549 cells. USP22 and its downstream proteins γH2AX and Sirt1 levels are upregulated in the cisplatin resistant A549/CDDP cell line. USP22 enhances DNA damage repair and induce cisplatin resistance by promoting the phosphorylation of histone H2AX via deubiquitinating histone H2A. In addition, USP22 decreases the acetylation of Ku70 by stabilizing Sirt1, thus inhibiting Bax-mediated apoptosis and inducing cisplatin resistance. The cisplatin sensitivity in cisplatin resistant A549/CDDP cells was restored by USP22 inhibition in vivo and vitro. In summary, our findings reveal the dual mechanism of USP22 involvement in cisplatin resistance that USP22 can regulate γH2AX-mediated DNA damage repair and Ku70/Bax-mediated apoptosis. USP22 is a potential target in cisplatin-resistant lung adenocarcinoma and should be considered in future therapeutic practice.